Active prospective national surveillance for congenital and neonatal varicella in Australia shows potential prevention opportunities - Jacina Walker; Suzy Teutsch; Anne Morris; Guy D. Eslick; Mahmudul Hassan Al Imam; Arifuzzaman Khan; Robert Booy; Elizabeth J Elliott; Gulam Khandaker (Vaccine: X, 2023)
To compare the incidence and outcomes of congenital and neonatal varicella in Australia in the pre-vaccination (1995–1997) and post-vaccination era (after 2005 to November 2020), active prospective national surveillance for congenital varicella syndrome (CVS) and neonatal varicella infection (NVI) was conducted through the Australian Paediatric Surveillance Unit (APSU). Compared with 1995–1997, there was a 91.5% reduction in the incidence of CVS and a 91.3% reduction in the incidence of NVI in 2009–2020. However, almost half of the mothers in 2009–2020 were born overseas and came from countries without a vaccination program. Although there has been a substantial and sustained decrease in the reported incidence of CVS and NVI in Australia since 2006, congenital and neonatal varicella infections persist. Thus, there is an opportunity for targeted screening of varicella in young migrant, asylum seeker and refugee women at risk of varicella infection and prioritisation for vaccination to prevent CVS and NVI.